2021
DOI: 10.3389/fonc.2021.756363
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Changes of AFP From Baseline to Recurrence as an Excellent Prognostic Factor of Hepatocellular Carcinoma After Locoregional Therapy: A 5-Year Prospective Cohort Study

Abstract: BackgroundAlthough many studies have confirmed the prognostic value of preoperative alpha-fetoprotein (AFP) in patients with hepatocellular carcinoma (HCC), the association between AFP at baseline (b-AFP), subsequent AFP at relapse (r-AFP), and AFP alteration and overall survival in HCC patients receiving locoregional therapy has rarely been systematically elucidated.Patients and MethodsA total of 583 subjects with newly diagnosis of virus-related HCC who were admitted to Beijing You ‘an Hospital, Capital Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As the size of the ablated tumor increased, so did the duration of ablation; additionally, complications became more likely ( 17 ). Multiple ablations may be employed for large or recurrent tumors ( 18 ). Because the tumor in this instance was big and close to the spleen, we chose to ablate a portion of it initially and then undergo another ablation after the tumor shrank.…”
Section: Discussionmentioning
confidence: 99%
“…As the size of the ablated tumor increased, so did the duration of ablation; additionally, complications became more likely ( 17 ). Multiple ablations may be employed for large or recurrent tumors ( 18 ). Because the tumor in this instance was big and close to the spleen, we chose to ablate a portion of it initially and then undergo another ablation after the tumor shrank.…”
Section: Discussionmentioning
confidence: 99%
“…AFP levels have been proven to correlate with the presence of vascular infiltration and the degree of differentiation ( 30 33 ). Moreover, our team’s previous study showed that RFS was shorter in N-P patients who were characterized by multiple tumors, large tumor diameter, and elevated transaminases, representing high liver tumor invasiveness and poor liver function, leading to poor prognosis ( 15 ). Although N-P patients have specific clinicopathological characteristics and prognoses, most prediction models have been developed without considering the specificity of liver biological function in the group of patients and can not reflect an accurate forecast ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ablation is the insertion of the electrodes into the tumor issue under the guidance of ultrasound, CT, and MRI, and generates frictional heat by applying high-frequency electrodes to the tissue to damage and destroy HCC cells, resulting in protein denaturation, loss of cell membrane integrity, mitochondrial dysfunction and inhibition of DNA replication (48)(49)(50). Both domestic and international studies and the previous study from our team showed that combination therapy by TACE and ablation improved overall and progression-free survival compared with TACE alone (15,(51)(52)(53)(54). Thus, we used TACE sequential ablation treatment, whose efficacy can be further demonstrated in multiple centers to improve the quality of life and extend the overall survival of more patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also demonstrated that AFP-negative HCC patients with a positive AFP level at the time of relapse have a higher mortality rate compared to those with a negative AFP level at relapse. 9 These findings suggest that AFP ratio may serve as a predictive indicator in AFP-negative HCC patients, although its impact on prognosis is still unclear.…”
Section: Introductionmentioning
confidence: 93%